Настанак и развој институције омбудсмана - Milkov, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
With regard to the establishment and development of the ombudsman institution, there are different views and even misconceptions. The Ombudsman Institution did not originate as an instrument for the protection of human rights. The Ombudsman was created by chance, due to the specific circumstances in which, at the beginning of the 18th century, the Swedish king Charles XII found himself. After the defeat of the Russian army at Poltava he found himself isolated in the Ottoman Empire. He wanted to control the situation in his homeland, and he set up his own representative, who in Swedish language is called the "Ombudsman". It is almost certain that an institution under this name would not have existed if there were no such events. However, as it often happens, once created institution continues to work and when it is no longer necessary. This happened with the Swedish Ombudsman, the Ombudsman was not abolished after the King's return, but he continued his work, with the role being changed. He became a parliamentary representative in charge of controlling the administration. The protection of human rights has been added to this institution only much later, mainly in the countries of the so-called new democracy. Since 1809, when the Swedish ombudsman was created, more than a hundred years have passed since this institution was not created by another country – Finland. However, the real expansion of the ombudsman came only after the creation of the Danish Ombudsman in 1953. Since then, the number of countries with an ombudsman has steadily increased. Today, it can be said that the ombudsman is a standard and necessary democratic institution, present in the vast majority of states.